Pengaruh Kualitas Pelayanan dan Kualitas Informasi Terhadap Kepuasan Konsumen Pembelian Online Produk Usaha Mikro Kecil Menengah di Kota Langsa - gunanjar, imam; Maulidan, Rahmat; Verinanda, Muhammad Ridwan; Syahputra, Rico; Sari, Maya Rizki; Zubir, Zubir (Sekolah Tinggi Ilmu Ekonomi Mahaputra Riau, 2025)
The focus of this research is based on the increasing use of digital platforms as the main medium for transactions, especially for MSMEs which aim to expand market reach and increase competitiveness. The population in this study consists of consumers who have made several purchases and consumed MSME products. From this population, a sample of 200 respondents was selected using accidental sampling or convenience sampling techniques. The findings show that service quality and information quality contribute significantly to consumer satisfaction. These variables collectively have a significant influence on consumer satisfaction. This research provides valuable insight for MSME practitioners in Langsa City, especially in understanding the importance of service quality and information quality in increasing consumer satisfaction. These findings can be used as strategic considerations to improve the quality of interactions with consumers and increase competitiveness in an increasingly competitive market.